Correlation of sociodemographic variables and interpersonal sources of stress at work among miners - Kulić, Ljiljana; Galjak, Milivoje; Jovanović, Jovana (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Some professions are somewhat more exposed to stress and have been the subject of research for a long time, and research of occupational stress among employees at workplaces with a special health risk is of a special significance. That is the case with miners. The aim of the study was an assessment of the relation between the sociodemographic variables and interpersonal sources of stress at work among miners. Methods. The study was designed as a cross-sectional study and covered 170 respondents, classified into two groups: a study group comprised of miners (n = 142) and a control group (n = 28) comprised of administrative workers. The research was conducted at the Occupational Medicine Service of the Health Center Zvečan and at the Institute of Occupational Medicine in Niš. The questionnaire on the basic sociodemographic indicators of respondents, the Intrapersonal and Interpersonal Related Stressors Questionnaire (IRS), the Work Ability Index Questionnaire (WAI), the General Health Questionnaire (GHQ), the Copenhagen Burnout Inventory (CBI) and the Questionnaire on the stressors were used in this research. Results. Statistically, the miners consumed alcohol significantly more than the respondents from the control group (68.30% vs. 25.00%; p < 0.001). Relative to age, there was a statistically significant difference in the subscales: demands (p = 0.037), control (p = 0.010), relations (p = 0.009) and change (p = 0.008). The control score values increased with age. The relations values were highest among the oldest respondents. The values of change decreased with age. Relative to exposed years of service (ERS), there was a statistically significant difference in the subscale relations; the miners with ERS longer than 15 years had a statistically significantly higher relations score (p = 0.003). The values of subscales control (p < 0.001), manager support (p = 0.010), relations (p < 0.001) and work role (p < 0.001) were statistically significantly lower among the miners compared to the control group. The values of subscales peer support (p = 0.002) and change (p < 0.001) were statistically significantly higher among the miners compared to the control group. Conclusion. The results indicate the correlation of sociodemographic variables with interpersonal sources of stress at work among the miners.The following prevention measures are proposed: adequate professional orientation, professional selection, professional adaptation, organizational measures, progressive development of knowledge and skills, development of good interpersonal relationships, strengthening the family-organization-company relation, relaxation techniques at the workplace, stress control, application of physiological techniques, application of cognitive techniques.